Syari’ah: Antara Kodifikasi Hukum dan Moral Islam (Telaah Peikira Muhaad “A’id Al-Ashmawi) - Haqqul Yaqin (Institut Ilmu Keislaman Zainul Hasan Genggong, 2015)
In the discourse of Islamic thought, shari'ah is a problematic word and debatable. Most scholars agree that sharia law contains benefit for the people human. But they differ in their opinions benefit as the purpose of sharia law. while Muhammad